Mediation effects of language anxiety and prior learning experience on academic speaking challenges and strategies among Libyan students in Malaysian universities - Halali, Ahlam Ali Salim; Ismail, Lilliati; Abd Samad, Arshad; Razali, Abu Bakar; Noordin, Nooreen (Sciedu Press, 2023)
This study examined the academic speaking challenges faced by Libyan students in Malaysian universities, explored the strategies they used to overcome these challenges, and investigated the influence of prior learning experience and language anxiety on their academic communication abroad. The research also highlighted the role of self-regulated learning in helping Libyan students tackle their academic challenges and implement effective communication strategies in their new international academic setting. The study employed an explanatory mixed-mode research design, involving a questionnaire with 223 respondents, interviews with 15 informants, and a focused group discussion. Field notes and member checks were used for validation. Correlational procedures, structural equation modeling (SEM), and bootstrapping resampling analyses were conducted to examine the relationships between variables, validate study models, and test research hypotheses. NVivo analysis was utilized to code and generate themes from interviews, focus group discussions, and field notes. Findings revealed that Libyan students in Malaysian universities displayed strong self-regulated learning characterized by positive motivation and self-awareness, enabling them to overcome communication challenges through the implementation of various strategies to achieve academic success. The study also demonstrated that language challenges, language anxiety, and prior experience influenced the adoption of academic speaking strategies. These results emphasize the need for stakeholders to address the negative prior experiences faced by Libyan international students and highlight the importance of further research on previous experiences and emotional factors to gain a deeper understanding of the learning experiences of international EFL students in higher education institutions.